Green supply chain practices, environmental management accounting and performance of Malaysian ISO 14001 manufacturing organisations - Wong, Wui Kiet (2019)
Globalisation and the growth of sustainable development have forced organisations to act sensitively toward environmental issues. The implementation of green supply chain practices (GSCPs) and environmental management accounting (EMAs) are gaining popularity as a management approach in facilitating organisations to identify positive environmental improvement activities to reduce environmental impacts and induce cost-saving. Nevertheless, studies revealed the GSCPs and EMAs remain minimally practised. Many organisations are not aware the significance of both to environmentally sustainable development. Moreover, the investigation of cost-saving leverages from the implementing of GSCP and EMA practices to environmental performance (ENP) and economic performance (ECP) is still ongoing. Therefore, the objective of this research is to develop a structural framework based on the natural resources-based view (NRBV) theory to empirically test the relationship between GSCPs, EMAs, ENP and ECP. A quantitative survey was employed, and a questionnaire was developed to collect data from Malaysian ISO 14001 certified organisations that have been registered for more than three years with SIRIM QAS International. A total of 399 postage surveys were distributed to the environmental management representatives (EMRs) who were the targeted respondents for this study. A total of 121 completed questionnaires were returned and yielded a response rate of 30.3%. To test the hypothesised relationship proposed by this study, Partial Least Square Structural Equation Modelling (PLS-SEM) was employed and analysed via the SmartPLS3 algorithms. The findings revealed that GSCPs directly and positively related to both EMAs and ENP but not directly to ECP. The relationship between GSCPs and ECP was indirect through ENP. Further, EMAs directly and positively related to ENP and ECP, and ENP was directly and positively related to ECP. It is also found that the mediating role of EMA was significant between GSCPs and ENP. This study provides a new mediating relationship and empirical insights into the current development of GSCPs, EMA, ENP and ECP. The results provide empirical support for the economic gain in the form of cost-saving that can be leveraged from the collective implementation of GSCPs and EMA. These are beneficial analyses to achieve cost reductions by improving ENP. Operational managers, supply chain managers, accountants and environmental management representatives are offered insights into how GSCP and EMA contribute to improving environmental and economic performance by implementing GSCPs and adopting relevant and reliable information from EMAs. Both physical and monetary information were significant in identifying the key sustainability drivers when making decisions concerning environmental protection. The results provide insights for managers and accountants to support better environmental investment, environmental costing determinations and provisions for environmental risk assessments.